Thyroid nodules with KRAS mutations are different from nodules with NRAS and HRAS mutations with regard to cytopathologic and histopathologic outcome characteristics. Issue 12 (12th August 2014) - Radkay, Lisa A.; Chiosea, Simion I.; Seethala, Raja R.; Hodak, Steven P.; LeBeau, Shane O.; Yip, Linwah; McCoy, Kelly L.; Carty, Sally E.; Schoedel, Karen E.; Nikiforova, Marina N.; Nikiforov, Yuri E.; Ohori, N. Paul
<x xml:space="preserve">Abstract</x> BACKGROUND Mutations in the RAS gene in the thyroid gland result in the activation of signaling pathways and are associated with a follicular growth pattern and the probability of a carcinoma outcome ranging from 74% to 87%. In the current study, the authors investigated the cytopathologic and histopathologic features of common RAS mutation subtypes. METHODS Malignant, indeterminate, and selected benign thyroid cytology cases were tested prospectively for the presence of NRAS61, HRAS61, and KRAS12/13 mutations. For each case, the Bethesda System for thyroid cytopathology diagnosis, additional cytologic descriptors, and surgical pathology outcomes were documented. The Fisher exact test and Wilcoxon 2‐sample test were used for statistical comparison between the groups. RESULTS A total of 204 thyroid fine‐needle aspiration cases with RAS mutations (93.6% of which were associated with indeterminate cytopathology diagnoses) and corresponding surgical pathology resection specimens were identified. The KRAS12/13 mutation was associated with a significantly lower carcinoma outcome (41.7%) when compared with HRAS61 (95.5%) and NRAS61 (86.8%) mutations (P<.0001). Furthermore, oncocytic change was observed in a significantly higher percentage of cytology and resection specimens with KRAS12/13 mutations (66.7% and 75.0%, respectively) in comparison with those with HRAS61 (4.5% and 4.5%, respectively) and NRAS61 (15.4% and 14.7%, respectively) mutations (P<.0001). RAS mutations also were identified in cases of poorly differentiated carcinoma (NRAS61), anaplastic carcinoma (HRAS61), and medullary thyroid carcinoma (HRAS61 and KRAS12/13). CONCLUSIONS Subclassification of RAS mutations in conjunction with cytopathologic evaluation improves presurgical risk stratification, provides better insight into lesional characteristics, and may influence patient management. In particular, KRAS12/13‐mutated thyroid nodules were found to be different from HRAS61‐mutated and NRAS61‐mutated nodules with regard to cytopathologic and surgical outcome characteristics. Cancer (Cancer Cytopathol) 2014;122:873–882. © 2014 American Cancer Society.